The relationship between social capital and objective welfare of cocoa farmer households in Tolada Village, North Luwu Regency, South Sulawesi, Indonesia - Heliawaty (EDP Sciences, 2021)
Social capital is an important aspect of developing more advanced agriculture. Community social capital, such as trust, mutual cooperation, networks and attitudes, play a major role in community behaviour, and if managed properly, it will be able to empower the community. Various elements of social capital found in rural areas are alleged to be able to contribute to the objective welfare of rural communities, especially farmers. This research uses s descriptive quantitative research method, namely the method used to measure and describe the data regarding the elements of social capital owned by cocoa farmers (trust and network) and their relationship with objective economic welfare. The purpose of this study was to determine the relationship between social capital and the objective welfare of cocoa farmer households. The results showed that the correlation value of social capital and objective welfare was in the medium category, where the social capital of the farmer's life took place in an intimate, mutual trust and could take advantage of the existing network to collaborate to solve agricultural problems.